Biogeochemical markers in juvenile Leach's storm-petrels (Hydrobates leucorhous) stranded offshore are distinct from inshore stranded juveniles and nestlings - Anne N.M.A. Ausems; Sophie Roy; Alexander L. Bond; Laura Crick; Joshua T. Cunningham; April Hedd; Laura A. McFarlane Tranquilla; Jennifer C. Rock; Robert A. Ronconi; Katharine R. Studholme; Christopher R.E. Ward; Sabina I. Wilhelm; et al. (Marine Pollution Bulletin, 2026)

Bioaccumulation of trace elements by Leach's storm-petrels (Hydrobates leucorhous) in the North and South Atlantic Ocean during the non-breeding period - Catherine Potvin; Manon Sorais; Robert A. Ronconi; Katharine R. Studholme; April Hedd; Alexander L. Bond; Vegard S. Bråthen; Sydney M. Collins; Laura Crick; Joshua T. Cunningham; Anne N.M.A. Ausems; David A. Fifield; et al. (Marine Pollution Bulletin, 2026)

Control of fall armyworm with Spodoptera frugiperda multiple nucleopolyhedrovirus in sweet corn cultivated under agroecological conditions - T. Cunningham; C. de la Colina; M. Pérez; G. Quintana; Marco D´Amico; M. Berretta; J. Niz; M. L. Ferrelli; R. Salvador (BioControl, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Sensory-specific satiety and the influence of variety on snack intake in school-aged children - Paige M. Cunningham; Cara T. Meehan; Kathleen L. Keller; Barbara J. Rolls (Appetite, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Fine-scale biochemical variation in Fucus serratus (Phaeophyceae): Point sampling vs bulk samples and implications for industrial applications - Rebecca E. McKinney; Eoghan Mánus Cunningham; Jack Burton; Stefan Kraan; Jaimie T. A. Dick; Pamela J. Walsh (Journal of Applied Phycology, 2026)
EU policies on nature restoration and sustainability open the door for Fucus cultivation, however, based on the applications of the biomass, industry will have to explicitly account for spatiotemporal fluctuations in biochemical profiles. In general, brown seaweeds show high levels of biochemical variation, adjusting polysaccharide, protein, lipid, and secondary metabolite profiles in response to physiochemical factors and biological interactions, which vary geographically and seasonally. Therefore, in this study we examined the fine-scale spatial variability in two high value components, the total phenolic and protein content of Fucus serratus across three sites in Strangford Lough, Northern Ireland at two timepoints. We assessed how sampling either homogenised bulk or point sampling of thalli could impact detection of variability on an inter- and intra-site scale in August 2024 and February 2025, finding a significant effect on the detection of fine-scale variation in biochemical composition. Homogenised bulk samples were able to display clearer relationships, with February collected samples always possessing a higher protein and phenolic content than August samples. Point sampled thalli displayed high variability, capturing the fine-scale intra-site and intra-specific variation. Homogenisation of biomass delivered a more reliable and reproducible assessment of F. serratus biochemical composition at fine-scale, balancing sensitivity to broad patterns (such as seasonal shifts) with robustness against the high variability observed in single-thallus measurements. Developing this sampling protocol can help deliver actionable, site-scale predictions of yield and metabolite trends, ensuring consistent bioproduct quality.

Remote-sensing methods for mapping eucalypt dieback: A systematic review - Weerach Charerntantanakul; John T. Burley; Marta Yebra; Adrienne Beth Nicotra; Saul Alan Cunningham; Matthew Theodore Brookhouse (Remote Sensing Applications: Society and Environment, 2026)

Design of a vectorized rubidium scalar magnetometer for SmallSat applications - Carolina T. Chism; Robert A. Marshall; Aldo Aguilar-Nadalini; Svenja Knappe; David Malaspina; K. Jeramy Hughes; Michaela Ellmeier; Sebastian Wankmueller; Conor Cunningham; Tyler Maydew; Orang Alem (Advances in Space Research, 2025)

Parasite induced changes in contact behaviour is affected by parasitic status of group members - Alex M. M. Morris; Giles T. Innocent; Emma J. A. Cunningham; Darren P. Croft; Spiridoula Athanasiadou; Michael R. Hutchings; Lesley A. Smith (Behavioral Ecology and Sociobiology, 2025)
Understanding how parasitism may affect social behavior and social networks is key to understanding the impact of infection on a population. Infection can disrupt social networks by altering the behavior of both infected individuals (e.g. by reducing activity) and the behavior of uninfected individuals (e.g. avoiding sick individuals), both of which can have an impact on social group dynamics and parasite transmission. Here we test experimentally how parasitism affects social contact behavior and social network structure using a common parasite infection of sheep. Three treatment groups, each with 4 replicate social groups were established (i) Parasitised; all lambs were infected with a parasitic nematode, (ii) Non-parasitised; all lambs remained uninfected (iii) Mixed; part of each group were infected, and part of the group remained uninfected. Contact behaviours of each individual were recorded using proximity loggers during four phases of infection (pre-parasite, pre-patent, patent-parasite, post-parasite). We found infected individuals in the parasitised and mixed groups reduced contact frequency following infection. Despite the reduction in contacts between infected animals in the mixed group, non-infected individual’s maintained pre-parasite levels of social interactions with their infected conspecifics. These results demonstrate how infection can impact the social behavior of all animals within a group, and how the expression of behavioral change may depend on the parasitic status of all group members and the response of uninfected conspecifics. Significance statement Parasitism is known to influence animal behavior and social interactions; however groups of animals will often contain individuals of different parasitic status. Understanding the behavioral response of both infected and uninfected members of a group is important to predict the consequences of infection throughout a population. We show, under experimental conditions, that parasitism not only reduces the frequency of contacts between infected lambs at the earliest stages of infection in both mixed and single-parasitic state groups, but also the degree of behavior change exhibited by infected animals is influenced by the parasitic status of other individuals within the group. We also show that although infected animals in mixed-state groups had reduced contact frequency with their infected groupmates, non-infected animal’s maintained pre-infection levels of social interactions.

Accumulation of benzotriazole UV-stabilizers in relation to ingested plastics and associated health metrics in Larus gulls feeding at a landfill in Atlantic Canada - Kerry Schutten; André Morrill; Zhe Lu; Akshaya Chandrashekar; Joshua T. Cunningham; Gregory J. Robertson; Mark L. Mallory; Claire M. Jardine; Jennifer F. Provencher (Journal of Hazardous Materials, 2025)

Forecasting drought using machine learning: a systematic literature review - Ricardo S. Oyarzabal; Leonardo B. L. Santos; Christopher Cunningham; Elisangela Broedel; Glauston R. T. de Lima; Gisleine Cunha-Zeri; Jerusa S. Peixoto; Juliana A. Anochi; Klaifer Garcia; Lidiane C. O. Costa; Luana A. Pampuch; Luz Adriana Cuartas; et al. (Natural Hazards, 2025)

Compressive strength and regional supply implications of rice straw and rice hull ashes used as supplementary cementitious materials - Patrick R. Cunningham; Li Wang; Somayeh Nassiri; Peter Thy; John T. Harvey; Bryan M. Jenkins; Sabbie A. Miller (Resources, Conservation and Recycling, 2025)

Inpatient referrals to a specialist falls and syncope service: prevalence of STOPPFall FRIDs and review of deprescribing patterns - D. O’Donnell; T. Zainal; K. Malomo; N. Fitzpatrick; C. Rice; L. Byrne; R. Briggs; C. Cunningham; R. A. Kenny; A. H. Lavan (European Journal of Clinical Pharmacology, 2025)

A Conceptual Framework for Measuring Ecological Novelty - Timothy L. Staples; Jessica Blois; Katie L. Cramer; Emer T. Cunningham; Maria Dornelas; Simon G. Haberle; Tina Heger; Wolfgang Kiessling; Anne E. Magurran; Aaron O'Dea; Amelia M. Penny; Volker C. Radeloff; et al. (Global Ecology and Biogeography, 2025)
Background Human pressures are driving the emergence of unprecedented, ‘novel’, ecological and environmental systems. The concept of novel (eco)systems is well accepted by the scientific community, but the use and measurement of novelty has outgrown initial definitions and critiques. There are still unresolved methodological and conceptual differences in quantifying novelty that prevent a unified research approach. Framework Here we present a conceptual framework and guidelines to unify past and future measurement of ecological novelty. Under this framework, novelty is a property of an ecological or environmental entity of interest. Novelty is quantified as the comparison between the target entity and a reference set, measured as the summary of degrees of difference across one or more dimensions. Choices in these components, particularly the reference set, can change resulting novelty measurements and inferences. Showcase We provide a case‐study to showcase our framework, measuring pre‐ and post‐European novelty in 99 pollen assemblages in Midwest USA forests. We paired this quantitative exploration with a five‐step process designed to improve the utility and outcomes of novelty analyses. Conclusions Quantitative novelty has immense value in studies of abrupt ecological change, linking climatic and ecological change, biotic interactions and invasions, species range shifts and fundamental theories. Our framework offers a unified overview and is also primed for integration into management and restoration workflows, providing consistent and robust measurements of novelty to support decision making, priority setting and resource allocation.

Evaluating the performance of a system model in predicting zooplankton dynamics: Insights from the Bering Sea ecosystem - Genoa Sullaway; Curry J. Cunningham; David Kimmel; Darren J. Pilcher; James T. Thorson (Fisheries Oceanography, 2025)
Understanding how ecosystem change influences fishery resources through trophic pathways is a key tenet of ecosystem‐based fishery management. System models (SM), which use numerical modeling to describe physical and biological processes, can advance inclusion of ecosystem and prey information in fisheries management; however, incorporating SMs in management requires evaluation against empirical data. The Bering Ecosystem Study Nutrient‐Phytoplankton‐Zooplankton (BESTNPZ) model is an SM (originally created by the Bering Ecosystem Study, which initiated in 2006 and was expanded by Kearney et al.) includes zooplankton biomass hindcasts for the Bering Sea. In the Bering Sea, zooplankton are an important prey item for fishery species, yet the zooplankton component of this SM has not been validated against empirical data. We compared empirical zooplankton data to BESTNPZ hindcast estimates for three zooplankton functional groups and found that the two sources of information are on different absolute scales. We found high correlation between relative seasonal biomass trends estimated by BESTNPZ and empirical data for large off‐shelf copepods ( Neocalanus spp.) and low correlations for large on‐shelf copepods and small copepods ( Calanus spp. and Pseudocalanus spp., respectively). To address these discrepancies, we constructed hybrid species distribution models (H‐SDM), which predict zooplankton biomass using the BESTNPZ hindcast and environmental covariates. We found that H‐SDMs offered marginal improvements over correlative species distribution models (C‐SDMs) relying solely on empirical data for spatial extrapolation and little improvement for most functional groups when forecasting short‐term temporal zooplankton biomass trends. Overall, we suggest that interpretation of current BESTNPZ hindcasts should be tempered by our understanding of key mismatches in absolute scale, seasonality, and annual indices between BESTNPZ and empirical data.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Plastic ingestion, accumulated heavy metals, and health metrics of four Larus gull species feeding at a coastal landfill in eastern Canada - Kerry Schutten; André Morrill; Akshaya Chandrashekar; Brian Stevens; E. Jane Parmley; Joshua T. Cunningham; Gregory J. Robertson; Mark L. Mallory; Claire Jardine; Jennifer F. Provencher (Journal of Hazardous Materials, 2024)

Temporal dynamics of Devonian reef communities: Insights into natural phase shifts and long-term resilience in the face of environmental variability - Amanda Godbold; Nina Clark; Emer T. Cunningham; David J. Bottjer; John M. Pandolfi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Opening the black box: New insights into the role of temperature in the marine distributions of Pacific salmon - Joseph A. Langan; Curry J. Cunningham; Jordan T. Watson; Skip McKinnell (Fish and Fisheries, 2024)
Pacific salmon ( Oncorhynchus spp.) spend much of their life near the ocean surface where climatic and oceanographic conditions affect their habitat and survival. Despite decades of study, critical knowledge gaps persist regarding their ecology and distributions. Consequently, it has been difficult to assess how environmental conditions influence the high‐seas distribution and habitat use of these culturally and socioeconomically important fishes, presenting challenges to fisheries managers trying to evaluate how climate change and fishing activities may impact salmon populations. We used a recently compiled, comprehensive database of historical coastal and high‐seas salmon survey data (1953–2022) in the North Pacific to fit species distribution models that (1) characterize the marine spatial distribution of six species of Oncorhynchus , (2) evaluate species‐specific temperature preferences, and (3) investigate how species' temperature preferences influence distribution. Sea surface temperature, along with seasonal migrations associated with spawning and feeding, significantly affects the distribution of all species, where the warm limits of estimated preferred thermal ranges were more similar than the cold limits. Furthermore, the distributions of some species appear more responsive to temperature than others and recently observed warm conditions have likely impacted realized ranges. These models have expanded our understanding of salmon ocean distributions and thermal niches by providing a unique window into this often unobserved but important part of the life cycle. They also serve as a baseline for future investigations into the mechanisms influencing salmon spatial ecology, responses to climate change, and vulnerability to harvest across the North Pacific.

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Predicting energy consumption of zero emission buses using route feature selection methods - L.A.W. Blades; T. Matthews; T.E. McGrath; J. Early; G. Cunningham; A. Harris (Transportation Research Part D: Transport and Environment, 2024)

BASIS: BioAnalysis SEDFIT integrated software for cGMP analysis of SV-AUC data - Alexander E. Yarawsky; Erik S. Gough; Valeria Zai-Rose; Natalya I. Figueroa; Hazel M. Cunningham; John W. Burgner; Michael T. DeLion; Lake N. Paul (European Biophysics Journal, 2024)

Unlocking the triad of age, year, and cohort effects for stock assessment: Demonstration of a computationally efficient and reproducible framework using weight-at-age - Matthew LH. Cheng; James T. Thorson; James N. Ianelli; Curry J. Cunningham (Fisheries Research, 2023)

Factors influencing mercury exposure in Arctic-breeding shorebirds - Marie Perkins; Iain J. Stenhouse; Richard B. Lanctot; Stephen Brown; Joël Bêty; Megan Boldenow; Jenny Cunningham; Willow English; River Gates; H. Grant Gilchrist; Marie-Andrée Giroux; Kirsten Grond; et al. (Ecotoxicology, 2023)

AAV analysis by sedimentation velocity analytical ultracentrifugation: beyond empty and full capsids - Alexander E. Yarawsky; Valeria Zai-Rose; Hazel M. Cunningham; John W. Burgner; Michael T. DeLion; Lake N. Paul (European Biophysics Journal, 2023)

Research needs, environmental concerns, and logistical considerations for incorporating livestock grazing into coastal upland habitat management - K. Gill; K.A. Chenier; A. Free; J. Goff; J.L. Pitchford; K. Cressman; M. Posten; E. Brunden; M. Shelton; K. Swanson; S.R. Cunningham; J. Garland; et al. (Journal of Environmental Management, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Historical reconstruction and social context of recreational fisheries: The Australian East Coast Barramundi - Carolina Chong‐Montenegro; Ruth H. Thurstan; Alexander B. Campbell; Emer T. Cunningham; John M. Pandolfi (Fisheries Management and Ecology, 2022)
Recreational fishing in Australia makes important contributions to local economies and fisheries harvests. Historical evaluations of the cumulative effects of exploitation for most recreationally targeted Australian fish stocks remain unexplored, as do the social and cultural contexts of recreational fishing. Historical newspaper articles were used to derive quantitative and qualitative catch data on Queensland's east coast barramundi, Lates calcarifer (Bloch), a popular species targeted by recreational fishers. Decadal‐scale catch rates (1869–1952) were reconstructed, as was the development of the fishery since its earliest documentation. Models indicated a significant decline in catch rates, from an average of 5.20 kg /fishing trip (95% confidence interval, 3.82–7.09) in 1870–3.24 kg/fishing trip (95% CI 2.72–3.87) in 1952. Variability in catch rates was associated with a spatial and seasonal interaction effect, with average catch rates differing among regions and seasons. Qualitative analysis showed a northward expansion of the fishery along the east coast, coinciding with increasing number of locations fished, establishment of organised fishing clubs in the 1900s and concerns of overexploitation starting in 1909. Integration of quantitative and qualitative analysis revealed past socio‐cultural factors and trends in the barramundi fishery, while building confidence in the reliability of inferences made from archival data sets.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Smoke on the Water: Comparative Assessment of Combined Thermal Shock Treatments for Control of Invasive Asian Clam, Corbicula fluminea - Neil E. Coughlan; Ross N. Cuthbert; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Gina Y. W. Vong; Emma Healey; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Jaimie T. A. Dick (Environmental Management, 2021)
Suppression of established populations of invasive alien species can be a complex and expensive process, which is frequently unsuccessful. The Asian clam, Corbicula fluminea (Müller, 1774), is considered a high impact invader that can adversely alter freshwater ecosystems and decrease their socioeconomic value. To date, C. fluminea continues to spread and persist within freshwater environments worldwide, despite repeated management attempts to prevent dispersal and suppress established populations. As extensive C. fluminea beds can often become exposed during low-water conditions, the direct application of hot or cold thermal shock treatments has been proposed as suitable mechanism for their control. Further, mechanical substrate disturbance may enhance the efficacy of thermal shock treatments by facilitating exposures to multiple layers of buried clams. In the present study, we advanced these methods by assessing combined applications of both hot and cold thermal shock treatments for control of C. fluminea , using steam spray (≥100 °C; 350 kPa), low- or high-intensity open-flame burns (~1000 °C) and dry ice (−78 °C). In a direct comparison of raking combined with hot thermal shock applications, both steam and high-intensity open-flame treatments tended to be most effective, especially following multiple applications. In addition, when hot thermal treatments are followed by a final cold shock (i.e. dry ice), steam treatments tended to be most effective. Further, when dry ice was applied either alone or prior to an application of a hot shock treatment, substantial if not complete C. fluminea mortality was observed. Overall, this study demonstrated that combined applications of hot and cold thermal shock treatments, applied following the disruption of the substrate, can substantially increase C. fluminea mortality compared to separate hot or cold treatments.

Steam and Flame Applications as Novel Methods of Population Control for Invasive Asian Clam (Corbicula fluminea) and Zebra Mussel (Dreissena polymorpha) - Neil E. Coughlan; Eoghan M. Cunningham; Stephen Potts; Diarmuid McSweeney; Emma Healey; Jaimie T. A. Dick; Gina Y. W. Vong; Kate Crane; Joe M. Caffrey; Frances E. Lucy; Eithne Davis; Ross N. Cuthbert (Environmental Management, 2020)
Control strategies for established populations of invasive alien species can be costly and complex endeavours, which are frequently unsuccessful. Therefore, rapid-reaction techniques that are capable of maximising efficacy whilst minimising environmental damage are urgently required. The Asian clam ( Corbicula fluminea Müller, 1774), and the zebra mussel ( Dreissena polymorpha Pallas, 1771), are invaders capable of adversely affecting the functioning and biodiversity of freshwater ecosystems. Despite efforts to implement substantial population-control measures, both species continue to spread and persist within freshwater environments. As bivalve beds often become exposed during low-water conditions, this study examined the efficacy of steam-spray (≥100 °C, 350 kPa) and open-flame burn treatments (~1000 °C) to kill exposed individuals. Direct steam exposure lasting for 5 min caused 100% mortality of C. fluminea buried at a depth of 3 cm. Further, combined rake and thermal shock treatments, whereby the substrate is disturbed between each application of either a steam or open flame, caused 100% mortality of C. fluminea specimens residing within a 4-cm deep substrate patch, following three consecutive treatment applications. However, deeper 8-cm patches and water-saturated substrate reduced maximum bivalve species mortality rates to 77% and 70%, respectively. Finally, 100% of D. polymorpha specimens were killed following exposure to steam and open-flame treatments lasting for 30 s and 5 s, respectively. Overall, our results confirm the efficacy of thermal shock treatments as a potential tool for substantial control of low-water-exposed bivalves. Although promising, our results require validation through upscaling to field application, with consideration of other substrate types, increased substrate depth, greater bivalve densities, non-target and long-term treatment effects.

Floral resources of an invasive shrub alter native bee communities at different vertical strata in forest-edge habitat - M. J. Cunningham-Minnick; T. O. Crist (Biological Invasions, 2020)

Driven by speculation, not by impact – the effects of plastic on fish species - Eoghan M. Cunningham; Konstadinos Kiriakoulakis; Jaimie T. A. Dick; Louise Kregting; Pia Schuchert; Julia D. Sigwart (Journal of Fish Biology, 2020)

High temperatures are associated with substantial reductions in breeding success and offspring quality in an arid-zone bird - T. M. F. N. van de Ven; A. E. McKechnie; S. Er; S. J. Cunningham (Oecologia, 2020)

Better off dead: assessment of aquatic disinfectants and thermal shock treatments to prevent the spread of invasive freshwater bivalves - Neil E. Coughlan; Stephanie J. Bradbeer; Ross N. Cuthbert; Eoghan M. Cunningham; Kate Crane; Stephen Potts; Joe M. Caffrey; Frances E. Lucy; Alison M. Dunn; Eithne Davis; Trevor Renals; Claire Quinn; et al. (Wetlands Ecology and Management, 2020)
Biosecurity protocols designed to prevent further spread of invasive alien species have become a key component of invader management strategies. Yet, the species-specific efficacy of many biosecurity treatments are frequently unclear or unknown. Invasive quagga, Dreissena bugensis , and zebra mussels, D. polymorpha , are a serious threat to freshwater ecosystems worldwide. Here, we examine the effectiveness of immersion (≤ 90 min) within 2% or 4% solutions for two commonly used disinfectants (Virasure® Aquatic and Virkon® Aquatic) to cause mortality of adult Dreissena bivalves . Further, we assessed the effectiveness of thermal treatments: steam spray (≥ 100 °C; ≤ 120 s); hot air (− 500 °C; ≤ 60 s); and dry ice exposure (− 78 °C; ≤ 300 g; 15 min). Complete mortality of D. polymorpha was observed following exposure to both disinfectants for 90 min, at both concentrations. However, high but incomplete mortality (40–90%) was recorded for D. bugensis across disinfectant treatments. For both species, complete mortality was achieved following 30 s of steam. In addition, 10 s of hot air and 15 min exposure to 300 g of dry ice can both completely killed groups of D. polymorpha . Overall, although the disinfectants did not cause complete mortality, it appears that relatively brief exposure to thermal treatments could be used to curtail the further spread of Dreissena species.

Inferring seasonal infection risk at population and regional scales from serology samples - Mark Q. Wilber; Colleen T. Webb; Fred L. Cunningham; Kerri Pedersen; Xiu‐Feng Wan; Kim M. Pepin (Ecology, 2020)
Accurate estimates of seasonal infection risk can be used by animal health officials to predict future disease risk and improve understanding of the mechanisms driving disease dynamics. It can be difficult to estimate seasonal infection risk in wildlife disease systems because surveillance assays typically target antibodies (serosurveillance), which are not necessarily indicative of current infection, and serosurveillance sampling is often opportunistic. Recently developed methods estimate past time of infection from serosurveillance data using quantitative serological assays that indicate the amount of antibodies in a serology sample. However, current methods do not account for common opportunistic and uneven sampling associated with serosurveillance data. We extended the framework of survival analysis to improve estimates of seasonal infection risk from serosurveillance data across population and regional scales. We found that accounting for the right‐censored nature of quantitative serology samples greatly improved estimates of seasonal infection risk, even when sampling was uneven in time. Survival analysis can also be used to account for common challenges when estimating infection risk from serology data, such as biases induced by host demography and continually elevated antibodies following infection. The framework developed herein is widely applicable for estimating seasonal infection risk from serosurveillance data in humans, wildlife, and livestock.

The costs of keeping cool: behavioural trade-offs between foraging and thermoregulation are associated with significant mass losses in an arid-zone bird - T. M. F. N. van de Ven; A. E. McKechnie; S. J. Cunningham (Oecologia, 2019)

Projected changes in Brook Trout and Brown Trout distribution in Wisconsin streams in the mid-twenty-first century in response to climate change - Matthew G. Mitro; John D. Lyons; Jana S. Stewart; Paul K. Cunningham; Joanna D. T. Griffin (Hydrobiologia, 2019)

Effects of historic and projected climate change on the range and impacts of an emerging wildlife disease - Stephen J. Price; William T. M. Leung; Christopher J. Owen; Robert Puschendorf; Chris Sergeant; Andrew A. Cunningham; Francois Balloux; Trenton W. J. Garner; Richard A. Nichols (Global Change Biology, 2019)
The global trend of increasing environmental temperatures is often predicted to result in more severe disease epidemics. However, unambiguous evidence that temperature is a driver of epidemics is largely lacking, because it is demanding to demonstrate its role among the complex interactions between hosts, pathogens, and their shared environment. Here, we apply a three‐pronged approach to understand the effects of temperature on ranavirus epidemics in UK common frogs, combining in vitro, in vivo, and field studies. Each approach suggests that higher temperatures drive increasing severity of epidemics. In wild populations, ranavirosis incidents were more frequent and more severe at higher temperatures, and their frequency increased through a period of historic warming in the 1990s. Laboratory experiments using cell culture and whole animal models showed that higher temperature increased ranavirus propagation, disease incidence, and mortality rate. These results, combined with climate projections, predict severe ranavirosis outbreaks will occur over wider areas and an extended season, possibly affecting larval recruitment. Since ranaviruses affect a variety of ectothermic hosts (amphibians, reptiles, and fish), wider ecological damage could occur. Our three complementary lines of evidence present a clear case for direct environmental modulation of these epidemics and suggest management options to protect species from disease.

Real-Time Monitoring with a Tablet App Improves Implementation of Treatments to Enhance Forest Structural Diversity - Colin T Maher; Emily Oja; Abigail Marshall; Matthew Cunningham; Lucas Townsend; Graham Worley-Hood; Luke Ruffner Robinson; Taylor Margot; Drew Lyons; Stuart Fety; Eryn E Schneider; Sean M A Jeronimo; et al. (Journal of Forestry, 2019)

Thermal conditions within tree cavities in ponderosa pine (Pinus ponderosa) forests: potential implications for cavity users - Kerri T. Vierling; Teresa J. Lorenz; Patrick Cunningham; Kelsi Potterf (International Journal of Biometeorology, 2018)

Clinostomum album n. sp. and Clinostomum marginatum (Rudolphi, 1819), parasites of the great egret Ardea alba L. from Mississippi, USA - Thomas G. Rosser; Neely R. Alberson; Ethan T. Woodyard; Fred L. Cunningham; Linda M. Pote; Matt J. Griffin (Systematic Parasitology, 2017)

Morphological, ecological and behavioural differentiation of sympatric profundal and pelagic Arctic charr (Salvelinus alpinus) in Loch Dughaill Scotland - O. E. Hooker; J. Barry; T. E. Van Leeuwen; A. Lyle; J. Newton; P. Cunningham; C. E. Adams (Hydrobiologia, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Network analysis of host–virus communities in bats and rodents reveals determinants of cross‐species transmission - Angela D. Luis; Thomas J. O'Shea; David T. S. Hayman; James L. N. Wood; Andrew A. Cunningham; Amy T. Gilbert; James N. Mills; Colleen T. Webb (Ecology Letters, 2015)
Bats are natural reservoirs of several important emerging viruses. Cross‐species transmission appears to be quite common among bats, which may contribute to their unique reservoir potential. Therefore, understanding the importance of bats as reservoirs requires examining them in a community context rather than concentrating on individual species. Here, we use a network approach to identify ecological and biological correlates of cross‐species virus transmission in bats and rodents, another important host group. We show that given our current knowledge the bat viral sharing network is more connected than the rodent network, suggesting viruses may pass more easily between bat species. We identify host traits associated with important reservoir species: gregarious bats are more likely to share more viruses and bats which migrate regionally are important for spreading viruses through the network. We identify multiple communities of viral sharing within bats and rodents and highlight potential species traits that can help guide studies of novel pathogen emergence.

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

ABO blood group and risk of epithelial ovarian cancer within the Ovarian Cancer Association Consortium - Elizabeth M. Poole; Margaret A. Gates; Brigit A. High; Stephen J. Chanock; Daniel W. Cramer; Julie M. Cunningham; Brooke L. Fridley; Simon A. Gayther; Ellen L. Goode; Edwin S. Iversen; Jolanta Lissowska; Rachel T. Palmieri Weber; et al. (Cancer Causes & Control, 2012)

Model‐guided fieldwork: practical guidelines for multidisciplinary research on wildlife ecological and epidemiological dynamics - Olivier Restif; David T. S. Hayman; Juliet R. C. Pulliam; Raina K. Plowright; Dylan B. George; Angela D. Luis; Andrew A. Cunningham; Richard A. Bowen; Anthony R. Fooks; Thomas J. O'Shea; James L. N. Wood; Colleen T. Webb (Ecology Letters, 2012)
Infectious disease ecology has recently raised its public profile beyond the scientific community due to the major threats that wildlife infections pose to biological conservation, animal welfare, human health and food security. As we start unravelling the full extent of emerging infectious diseases, there is an urgent need to facilitate multidisciplinary research in this area. Even though research in ecology has always had a strong theoretical component, cultural and technical hurdles often hamper direct collaboration between theoreticians and empiricists. Building upon our collective experience of multidisciplinary research and teaching in this area, we propose practical guidelines to help with effective integration among mathematical modelling, fieldwork and laboratory work. Modelling tools can be used at all steps of a field‐based research programme, from the formulation of working hypotheses to field study design and data analysis. We illustrate our model‐guided fieldwork framework with two case studies we have been conducting on wildlife infectious diseases: plague transmission in prairie dogs and lyssavirus dynamics in A merican and A frican bats. These demonstrate that mechanistic models, if properly integrated in research programmes, can provide a framework for holistic approaches to complex biological systems.

Effects of pramipexole on the reinforcing effectiveness of stimuli that were previously paired with cocaine reinforcement in rats - Gregory T. Collins; Alyssa R. Cunningham; Jianyong Chen; Shaomeng Wang; Amy H. Newman; James H. Woods (Psychopharmacology, 2012)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Analytical model for screening potential CO2 repositories - Roland T. Okwen; Mark T. Stewart; Jeffrey A. Cunningham (Computational Geosciences, 2011)

Photobleaching on Photonic Crystal Enhanced Fluorescence Surfaces - Vikram Chaudhery; Meng Lu; Cheng Sheng Huang; Sherine George; Brian T. Cunningham (Journal of Fluorescence, 2011)

Impact of hydrographic data assimilation on the modelled Atlantic meridional overturning circulation - G. C. Smith; K. Haines; T. Kanzow; S. Cunningham (Ocean Science, 2010)
Here we make an initial step toward the development of an ocean assimilation system that can constrain the modelled Atlantic Meridional Overturning Circulation (AMOC) to support climate predictions. A detailed comparison is presented of 1° and 1/4° resolution global model simulations with and without sequential data assimilation, to the observations and transport estimates from the RAPID mooring array across 26.5° N in the Atlantic. Comparisons of modelled water properties with the observations from the merged RAPID boundary arrays demonstrate the ability of in situ data assimilation to accurately constrain the east-west density gradient between these mooring arrays. However, the presence of an unconstrained "western boundary wedge" between Abaco Island and the RAPID mooring site WB2 (16 km offshore) leads to the intensification of an erroneous southwards flow in this region when in situ data are assimilated. The result is an overly intense southward upper mid-ocean transport (0–1100 m) as compared to the estimates derived from the RAPID array. Correction of upper layer zonal density gradients is found to compensate mostly for a weak subtropical gyre circulation in the free model run (i.e. with no assimilation). Despite the important changes to the density structure and transports in the upper layer imposed by the assimilation, very little change is found in the amplitude and sub-seasonal variability of the AMOC. This shows that assimilation of upper layer density information projects mainly on the gyre circulation with little effect on the AMOC at 26° N due to the absence of corrections to density gradients below 2000 m (the maximum depth of Argo). The sensitivity to initial conditions was explored through two additional experiments using a climatological initial condition. These experiments showed that the weak bias in gyre intensity in the control simulation (without data assimilation) develops over a period of about 6 months, but does so independently from the overturning, with no change to the AMOC. However, differences in the properties and volume transport of North Atlantic Deep Water (NADW) persisted throughout the 3 year simulations resulting in a difference of 3 Sv in AMOC intensity. The persistence of these dense water anomalies and their influence on the AMOC is promising for the development of decadal forecasting capabilities. The results suggest that the deeper waters must be accurately reproduced in order to constrain the AMOC.

Comparison of the DNA methylation profiles of human peripheral blood cells and transformed B-lymphocytes - Yan V. Sun; Stephen T. Turner; Jennifer A. Smith; Pamela I. Hammond; Alicia Lazarus; Jodie L. Van De Rostyne; Julie M. Cunningham; Sharon L. R. Kardia (Human Genetics, 2010)

The contribution of eastern-boundary density variations to the Atlantic meridional overturning circulation at 26.5° N - M. P. Chidichimo; T. Kanzow; S. A. Cunningham; W. E. Johns; J. Marotzke (Ocean Science, 2010)
We study the contribution of eastern-boundary density variations to sub-seasonal and seasonal anomalies of the strength and vertical structure of the Atlantic Meridional Overturning Circulation (AMOC) at 26.5° N, by means of the RAPID/MOCHA mooring array between April 2004 and October 2007. The major density anomalies are found in the upper 500 m, and they are often coherent down to 1400 m. The densities have 13-day fluctuations that are apparent down to 3500 m. The two strategies for measuring eastern-boundary density – a tall offshore mooring (EB1) and an array of moorings on the continental slope (EBH) – show little correspondence in terms of amplitude, vertical structure, and frequency distribution of the resulting basin-wide integrated transport fluctuations, implying that there are significant transport contributions between EB1 and EBH. Contrary to the original planning, measurements from EB1 cannot serve as backup or replacement for EBH: density needs to be measured directly at the continental slope to compute the full-basin density gradient. Fluctuations in density at EBH generate transport variability of 2 Sv rms in the AMOC, while the overall AMOC variability is 4.8 Sv rms. There is a pronounced deep-reaching seasonal cycle in density at the eastern boundary, which is apparent between 100 m and 1400 m, with maximum positive anomalies in spring and maximum negative anomalies in autumn. These changes drive anomalous southward upper mid-ocean flow in spring, implying maximum reduction of the AMOC, and vice-versa in autumn. The amplitude of the seasonal cycle of the AMOC arising from the eastern-boundary densities is 5.2 Sv peak-to-peak, dominating the 6.7 Sv peak-to-peak seasonal cycle of the total AMOC. Our analysis suggests that the seasonal cycle in density may be forced by the strong near-coastal seasonal cycle in wind stress curl.

Corrigendum to "Observed and simulated estimates of the meridional overturning circulation at 26.5° N in the Atlantic" published in Ocean Sci., 5, 575–589, 2009 - J. Baehr; S. Cunningham; H. Haak; P. Heimbach; T. Kanzow; J. Marotzke (Ocean Science, 2010)

Adjustment of the basin-scale circulation at 26° N to variations in Gulf Stream, deep western boundary current and Ekman transports as observed by the Rapid array - H. L. Bryden; A. Mujahid; S. A. Cunningham; T. Kanzow (Ocean Science, 2009)
The Rapid instrument array across the Atlantic Ocean along 26° N provides unprecedented monitoring of the basin-scale circulation. A unique feature of the Rapid array is the combination of full-depth moorings with instruments measuring temperature, salinity, pressure time series at many depths with co-located bottom pressure measurements so that dynamic pressure can be measured from surface to bottom. Bottom pressure measurements show a zonally uniform rise (and fall) of bottom pressure of 0.015 dbar on a 5 to 10 day time scale, suggesting that the Atlantic basin is filling and draining on a short time scale. After removing the zonally uniform bottom pressure fluctuations, bottom pressure variations at 4000 m depth against the western boundary compensate instantaneously for baroclinic fluctuations in the strength and structure of the deep western boundary current so there is no basin-scale mass imbalance resulting from variations in the deep western boundary current. After removing the mass compensating bottom pressure, residual bottom pressure fluctuations at the western boundary just east of the Bahamas balance variations in Gulf Stream transport. Again the compensation appears to be especially confined close to the western boundary. Thus, fluctuations in either Gulf Stream or deep western boundary current transports are compensated in a depth independent (barotropic) manner very close to the continental slope off the Bahamas. In contrast, compensation for variations in wind-driven surface Ekman transport appears to involve fluctuations in both western basin and eastern basin bottom pressures, though the bottom pressure difference fluctuations appear to be a factor of 3 too large, perhaps due to an inability to resolve small bottom pressure fluctuations after removal of larger zonal average, baroclinic, and Gulf Stream pressure components. For 4 tall moorings where time series dynamic height (geostrophic pressure) profiles can be estimated from sea surface to ocean bottom and bottom pressure can be added, there is no general correlation between surface dynamic height and bottom pressure. Dynamic height on each mooring is strongly correlated with sea surface height from satellite observations and the variability in both dynamic height and satellite sea surface height decrease sharply as the western boundary is approached.

A label-free photonic crystal biosensor imaging method for detection of cancer cell cytotoxicity and proliferation - Leo L. Chan; Saujanya L. Gosangari; Kenneth L. Watkin; Brian T. Cunningham (Apoptosis, 2007)

Phosphate nutrition effects on growth, phosphate transporter transcript levels and physiology of alfalfa cells - S. F. Abu. Qamar; T. G. Sors; S. M. Cunningham; B. C. Joern; J. J. Volenec (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Anomalous gradient winds in the subtropical jet stream and interpretations of forecast failures - T. N. Krishnamurti; P. Cunningham; K. Rajendran (Meteorology and Atmospheric Physics, 2005)

The role of protein kinase C in regulating equine eosinophil adherence and superoxide production - M. F. Sepulveda; E. C. Greenaway; M. Avella; N. T. Goode; F. M. Cunningham (Inflammation Research, 2005)

Causes and Effects of Temporospatial Declines of Gyps Vultures in Asia - D. J. Pain; A. A. Cunningham; P. F. Donald; J. W. Duckworth; D. C. Houston; T. Katzner; J. Parry‐Jones; C. Poole; V. Prakash; P. Round; R. Timmins (Conservation Biology, 2003)

Reply to the comment by C.S. Spirakis - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1999)

Dissipation of Phloxine B and Uranine in Protein Bait Sprayed in a Coffee Field for the Suppression of Mediterranean Fruit Fly - J. P. Alcantara-Licudine; R. T. Cunningham; N. J. Liquido; G. T. McQuate; Q. X. Li (Bulletin of Environmental Contamination and Toxicology, 1999)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

Hydrothermal uranium deposits containing molybdenum and fluorite in the Marysvale volcanic field, west-central Utah - C. G. Cunningham; J. D. Rasmussen; T. A. Steven; R. O. Rye; P. D. Rowley; S. B. Romberger; J. Selverstone (Mineralium Deposita, 1998)

Human cationic amino acid transporter gene hCAT-2 is assigned to 8p22 but is not the causative gene in lysinuric protein intolerance - T. Lauteala; Nina Horelli-Kuitunen; Ellen Closs; Marja-Liisa Savontaus; Mari Lukkarinen; Olli Simell; James Cunningham; Aarno Palotie; Pertti Aula (Human Genetics, 1997)

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Portage: A new early-maturing, round white table potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1995)

Prestile: A new round white potato variety - A. F. Reeves; G. A. Porter; C. E. Cunningham; R. J. Nickeson; F. E. Manzer; T. M. Work; A. A. Davis; E. S. Plissey (American Journal of Potato Research, 1994)

Factors governing the adaptation of cells in area-17 of the cat visual cortex - T. Maddess; M. E. McCourt; B. Blakeslee; R. B. Cunningham (Biological Cybernetics, 1988)

Wauseon: A new potato variety resistant to golden nematode with good processing quality - C. E. Cunningham; R. V. Akeley; L. C. Peterson; T. E. Snyder (American Journal of Potato Research, 1968)

Replication and cytopathogenicity of avian infectious bronchitis virus in chicken embryo kidney cells - T. G. Akers; C. H. Cunningham (Archives of Virology, 1968)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)